Digitalisation for Health — Some Economic Aspects - Beate Jochimsen (Wirtschaftsdienst)
Abstract When it comes to digitalising healthcare, Germany lags way behind other countries. In its 2021 report, the Health System Advisory Council discusses a strategy to overcome this shortcoming, i. e. the digitalisation of the German healthcare system. The idea is to shape digitalisation in a way that healthcare provision is improved with patients’ well-being in mind. Therefore, market failures in digital health markets have to be addressed as well as the chances and challenges that come with the usage of large amounts of data. Furthermore, this article highlights the potential of the electronic health record (EHR) and of the digital health app market and discusses requirements for reaching environmental and social sustainability within the context of the digitalisation of health.